Prescription Rates and Prognostic Implications of Optimally Targeted Guideline-Directed Medical Treatment in Heart Failure and Atrial Fibrillation: Insights From The MISOAC-AF Trial. Issue 3 (March 2023) - Moysidis, Dimitrios V.; Kartas, Anastasios; Samaras, Athanasios; Papazoglou, Andreas S.; Patsiou, Vasiliki; Bekiaridou, Alexandra; Baroutidou, Amalia; Tsagkaris, Christos; Karagiannidis, Efstratios; Daios, Stylianos; Anastasiou, Vasileios; Tsalikakis, Dimitrios; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Heart failure (HF) and atrial fibrillation (AF) commonly coexist in real-life clinical practice. Among patients with HF with reduced ejection fraction (HFrEF) or HF with mildly reduced ejection fraction (HFmrEF), guidelines call for evidence-based target doses of renin–angiotensin–aldosterone system inhibitors and beta-blockers. However, target doses of guideline-directed medical treatment (GDMT) are often underused in real-world conditions, including HF–AF comorbidity. This retrospective cohort study of a randomized trial (Motivational Interviewing to Support Oral AntiCoagulation adherence in patients with nonvalvular AF) included hospitalized patients with AF and HFrEF or HFmrEF. Optimally targeted GDMT was defined as intake of evidence-based target doses of renin–angiotensin–aldosterone system and beta-blockers at 3 months after discharge. Rates of optimally targeted GDMT achievement across the baseline estimated glomerular filtration rate (eGFR) were assessed. Independent predictors of nontargeted GDMT and its association with all-cause mortality and the composite of cardiovascular death or HF hospitalization were assessed by regression analyses. In total, 374 patients with AF and HFrEF or HFmrEF were studied. At 3 months after discharge, 30.7% received target doses of GDMT medications. The rate of optimally targeted GDMT was reduced by 11% for every 10 mg/min/1.73 m 2 decrease in baseline eGFR [adjusted β = 0.99; 95% confidence interval (CI), 0.98–0.99] levels. After a median 31-month follow-up period, 37.8% patients in the optimally targeted GDMT group died, as compared with 67.8% (adjusted hazard ratio: 1.49; 95% CI, 1.05–2.13) in the nontargeted GDMT group. The risk of cardiovascular death or HF hospitalization was also higher in these patients (adjusted hazard ratio: 1.60; 95% CI, 1.17–2.20). Target doses of all HF drugs were reached in roughly one-third of patients with AF and HFrEF or HFmrEF 3 months after hospital discharge. Nontargeted GDMT was more frequent across lower eGFR levels and was associated with worse outcomes.